ECONOMIC SECURITY OF THE STATE IN THE CONDITIONS OF DIGITAL TRANSFORMATION: IMPERATIVITIES OF IMPLEMENTING ARTIFICIAL INTELLIGENCE AND CYBER RESILIENCE - Maslak, Mariya; Sukhomlyn, Larysa; Hlazunova, Olha; Kulinichev, Petro (Current Problems of Sustainable Development, 2026)
The article examines the theoretical and methodological principles and practical aspects of ensuring the economic security of the state in the era of rapid development of artificial intelligence (AI) technologies and global digitalization. The key macroeconomic trends, the dynamics of global private investments in AI and their impact on global and national GDP are analyzed. The concept of cyber resilience as a multi-level system, which is the foundation of macroeconomic stability in conditions of hybrid threats and full-scale war, is substantiated. The essence of Ukraine’s national strategy for integrating AI into the public administration system (WINWIN strategy) is revealed and the state’s positions in international rankings (in particular, the Government AI Readiness Index 2025) are determined. Based on a large-scale empirical study (AI Focus 2026), the industry specifics of the implementation of AI by Ukrainian business are analyzed. The authors suggest strengthening economic security based on the integration of European cyber resilience practices and the implementation of a risk-oriented model of labor market regulation.
Keywords: economic security; artificial intelligence; digital transformation; cyber resilience; innovative development; investments; national strategy; micro and macro analysis; sustainability; labor market; socio- economic relations